“You Have to Separate the Sinner From the Sin”: Clinician’s Approaches to Psychological Assessments With Men who Have Sexually Offended - Chawke, Gemma (International journal of offender therapy and comparative criminology, 2020)
Men who have sexually offended are often referred for presentence psychological assessments to determine factors which contributed to offending, identify risk of recidivism, and develop treatment recommendations. The accuracy of assessments is largely reliant on the cooperation of the assessee. Despite the significant legal and emotional consequences, how clinicians approach these assessments, attempt to engage assessees, and overcome resistance have not been investigated. This research sought to develop an understanding of the clinicians’ experience of conducting the assessment. How clinicians approach interviews with men who have sexually offended and the techniques they use were explored. Six interviews were conducted with qualified psychologists, at a private practice, whose role included conducting psychological assessments across a range of forensic matters. The findings, reached using Interpretative Phenomenological Analysis, highlighted the relational/social nature of the interaction and the clinicians’ experience of a somewhat blurred line in practice between forensic assessments and therapeutic endeavours.